Enhanced Security Mechanism Using Hybrid Approach of Watermarking - Mohal, Deepakshi; Sharma, Sandeep (International Journal of Computer Sciences and Engineering, 2019)
In today’s era the information is represented with the help of digital system. With the advancement of technology , now a days data is transmitted from source to destination with the help of images. Images are the source of data transmission. Data transmission through images is more secure as compared to the transmission through networked medium. In networked medium, the text can be easily sent and sometimes affected or may be harm by some third party or others. In this paper, we have provided two way security mechanism. Firstly, we have encrypted the text in the image and then in second phase we have placed one image on another image. Hence it is a two way security mechanism. Proposed system uses the hybridization of SVD-SLT techniques to secure the image and achieve better results in terms of accuracy. Two phases of digital image watermarking are used one of which is encryption and another is decryption. SVD (Singular Value Decomposition) will divide the image into parts and SLT (Slant Let Transformation) will merge two images overall resulting in watermarking. The result improvement is indicated through performance analysis with parameters PSNR, SNR, SSIM and through proposed mechanism 15% improvement is observed.